Investigating motivating factors for sound hospital waste management. (2nd August 2016) - Ali, Mustafa; Wang, Wenping; Chaudhry, Nawaz
ABSTRACT: Sustainable management of hospital waste requires an active involvement of all key players. This study aims to test the hypothesis that three motivating factors, namely, Reputation, Liability, and Expense, influence hospital waste management. The survey for this study was conducted in two phases, with the pilot study used for exploratory factor analysis and the subsequent main survey used for cross-validation using confirmatory factor analysis. The hypotheses were validated through one-sample t tests. Correlations were established between the three motivating factors and organizational characteristics of hospital type, location, category, and size. The hypotheses were validated, and it was found that the factors of Liability and Expense varied considerably with respect to location and size of a hospital. The factor of Reputation, however, did not exhibit significant variation. In conclusion, concerns about the reputation of a facility and an apprehension of liability act as incentives for sound hospital waste management, whereas concerns about financial costs and perceived overburden on staff act as disincentives. Implications : This paper identifies the non economic motivating factors that can be used to encourage behavioral changes regarding waste management at hospitals in resource constrained environments. This study discovered that organizational characteristics such as hospital size and location cause the responses to vary among the subjects. Hence a policy maker must take into account the institutional setting before introducing a change geared towards better waste management outcomes across hospitals. This study covers a topic that has hitherto been neglected in resource constrained countries. Thus it can be used as one of the first steps to highlight and tackle the issue.